Assessment of hydroplanting techniques and herbicide tolerance of two native Hawaiian groundcovers with roadside re-vegetation potential - Baldos, Orville C. (Ann Arbor Michigan ProQuest LLC, 2009)
Roadside re-vegetation utilizing native groundcovers is a new initiative in Hawaiʻi. To develop establishment and maintenance protocols, large-scale propagation and selective weed control techniques for potential species need to be tested. This study evaluated hydroplanting techniques and screened pre- and post-emergence herbicides for establishing Fimbristylis cymosa and Sporobolus virginicus. Hydroplanting trials indicate that F. cymosa can be efficiently established through hydroseeding while S. virginicus can be hydromulched using auxin treated apical cuttings. Oxadiazon and oryzalin can be safely used in transplanted F. cymosa plugs but not seedlings. Fluazifop-p-butyl and aminopyralid can be safely applied in plants [greater than or equal to] 28 days old while sulfosulfuron should be spot sprayed. For S. virginicus, oxadiazon, oxyfluorfen, sulfosulfuron and aminopyralid can be used for transplanted plugs while carfentrazone + MCPA + mecoprop + dicamba and triclopyr should only be spot sprayed. Information gathered from the study has been incorporated into establishment protocols for the two species -- Abstract.
Thesis (Ph.D.)--University of Hawaii, 2009.
Keywords: Fimbristylis -- Hawaii; Sporobolus virginicus -- Hawaii; Ground cover plants -- Hawaii